Studi Kritis Terhadap Pendidikan Sekuler: Dampak Serta Refleksi Filsafat Pendidikan Islam - karumiadri; Afifuddin Harisah (Advances In Education Journal, 2025)
Education in Indonesia faces serious challenges not only in academic quality but also in the moral and identity aspects of students. The widespread phenomenon of male students dancing on social media and school stages as a form of artistic expression reflects a value crisis and a shift in educational paradigms detached from religious and cultural values. Secular education, which emphasizes cognitive aspects without integrating spiritual and moral values, has led to an identity vacuum and weak character formation. This article examines the impact of Western secular education on religious and social values and offers a reflection on Islamic educational philosophy as an integrative solution that emphasizes the connection between knowledge, faith, and adab (proper conduct). The proposed policy implications include the integration of religious and cultural values into the curriculum, strengthening character education based on ta’dīb, reorienting ethical arts education, and supervising and guiding the use of digital media. Thus, a reconstruction of the national education system grounded in moral values and local wisdom is necessary to develop individuals who are knowledgeable, faithful, and well-mannered.